Comprehensive Secondary Metabolite Profiling Toward Delineating the Solid and Submerged-State Fermentation of Aspergillus oryzae KCCM 12698 - Son, Su Y.; Lee, Sunmin; Singh, Digar; Lee, Na-Rae; Lee, Dong-Yup; Lee, Choong H. (Frontiers in Microbiology, 2018)
Aspergillus oryzae has been commonly used to make koji, meju, and soy sauce in traditional food fermentation industries. However, the metabolic behaviors of A. oryzae during fermentation in various culture environments are largely uncharacterized. Thus, we performed time resolved (0, 4, 8, 12, 16 day) secondary metabolite profiling for A. oryzae KCCM 12698 cultivated on malt extract agar and broth (MEA and MEB) under solid-state fermentation (SSF) and submerged fermentation (SmF) conditions using the ultrahigh performance liquid chromatography – linear trap quadrupole – ion trap – mass spectrometry (UHPLC – LTQ – IT – MS/MS) followed by multivariate analyses. We observed the relatively higher proportions of coumarins and oxylipins in SSF, whereas the terpenoids were abundant in SmF. Moreover, we investigated the antimicrobial efficacy of metabolites that were extracted from SSF and SmF. The SSF extracts showed higher antimicrobial activities as compared to SmF, with higher production rates of bioactive secondary metabolites viz., ketone-citreoisocoumarin, pentahydroxy-anthraquinone, hexylitaconic acid, oxylipins, and saturated fatty acids. The current study provides the underpinnings of a metabolomic framework regarding the growth and bioactive compound production for A. oryzae under the primarily employed industrial cultivation states. Furthermore, the study holds the potentials for rapid screening and MS-characterization of metabolites helpful in determining the consumer safety implications of fermented foods involving Koji mold.